Over-challenging Mothers: Motherhood after Assisted Reproductive Technology - Tahereh Sadeghi; Nooredin Mohammadi; Ali Mohammadpour; Mohammad Abbasi (Mashhad University of Medical Sciences, 2019)
Background & aim: The experience of having a child is a new experience that can be challenging for mothers. However, this experience can be different for mothers who are subjected to assisted reproduction techniques, compared to mothers with normal fertility experience. The assisted reproductive techniques influence the attitudes and expectations of mothers towards their children, as well as the mother-child relationship. This study aimed to investigate the challenges mothers face after assisted reproduction techniques. Methods: This study was conducted using a descriptive-interpretive phenomenological approach. The participants in this study included a total of 13 ART mothers, who took part in 21 in-depth interviews. Data were collected using semi-structured interviews. Six methodical activities introduced by van-Manen, were used during data collection, data analysis, and reporting the findings. Results: Challenges of mothers who had children through assisted reproduction techniques was summarized in the main theme of "Over Challenging Mothers".  This theme incorporated into three sub-themes: (1) child-centered maternity; (2) maternity in an aura of fear; (3) doubts in accepting the maternal role.. Conclusion: Undoubtedly, the experience of motherhood through assisted reproduction techniques is a challenging and stressful condition. In fact, this experience is a big challenge for mothers since these mothers used to be nulliparous. They may feel considerable anxiety about their child's health. Most of these mothers had their newborns after a long period of time, emotional investment, difficulty, and anxiety. These experiences lead to the emergence of the main theme of over challenging mother.